Biomechanical performance of the novel assembled uncovertebral joint fusion cage in single-level anterior cervical discectomy and fusion: A finite element analysis - Zhang, Xiang; Yang, Yi; Shen, Yi-Wei; Zhang, Ke-Rui; Ma, Li-Tai; Ding, Chen; Wang, Bei-Yu; Meng, Yang; Liu, Hao (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Anterior cervical discectomy and fusion (ACDF) is widely accepted as the gold standard surgical procedure for treating cervical radiculopathy and myelopathy. However, there is concern about the low fusion rate in the early period after ACDF surgery using the Zero-P fusion cage. We creatively designed an assembled uncoupled joint fusion device to improve the fusion rate and solve the implantation difficulties. This study aimed to assess the biomechanical performance of the assembled uncovertebral joint fusion cage in single-level ACDF and compare it with the Zero-P device. Methods: A three-dimensional finite element (FE) of a healthy cervical spine (C2−C7) was constructed and validated. In the one-level surgery model, either an assembled uncovertebral joint fusion cage or a zero-profile device was implanted at the C5–C6 segment of the model. A pure moment of 1.0 Nm combined with a follower load of 75 N was imposed at C2 to determine flexion, extension, lateral bending, and axial rotation. The segmental range of motion (ROM), facet contact force (FCF), maximum intradiscal pressure (IDP), and screw−bone stress were determined and compared with those of the zero-profile device. Results: The results showed that the ROMs of the fused levels in both models were nearly zero, while the motions of the unfused segments were unevenly increased. The FCF at adjacent segments in the assembled uncovertebral joint fusion cage group was less than that that of the Zero-P group. The IDP at the adjacent segments and screw–bone stress were slightly higher in the assembled uncovertebral joint fusion cage group than in those of the Zero-P group. Stress on the cage was mainly concentrated on both sides of the wings, reaching 13.4–20.4 Mpa in the assembled uncovertebral joint fusion cage group. Conclusion: The assembled uncovertebral joint fusion cage provided strong immobilization, similar to the Zero-P device. When compared with the Zero-P group, the assembled uncovertebral joint fusion cage achieved similar resultant values regarding FCF, IDP, and screw–bone stress. Moreover, the assembled uncovertebral joint fusion cage effectively achieved early bone formation and fusion, probably due to proper stress distributions in the wings of both sides.